2020
DOI: 10.1128/msphere.00685-20
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Positive Chemotaxis in the Protozoan Pathogen Trypanosoma brucei

Abstract: To complete its infectious cycle, the protozoan parasite Trypanosoma brucei must navigate through diverse tissue environments in both its tsetse fly and mammalian hosts. This is hypothesized to be driven by yet unidentified chemotactic cues. Prior work has shown that parasites engaging in social motility in vitro alter their trajectory to avoid other groups of parasites, an example of negative chemotaxis. However, movement of T. brucei toward a stimulus, positive chemotaxis, has so far not been reported. Here,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 56 publications
0
22
0
Order By: Relevance
“…Interestingly, there is strong evidence that CARP3 is N-myristoylated 40 This would enable parasites to follow cues provided by the fly as they migrate to different compartments. It is established that procyclic forms respond chemotactically to other effectors 20,21 , but their identities are unknown. Chemotaxis may also explain how parasites in the mammalian host disperse from the bloodstream into other tissues [42][43][44] .…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, there is strong evidence that CARP3 is N-myristoylated 40 This would enable parasites to follow cues provided by the fly as they migrate to different compartments. It is established that procyclic forms respond chemotactically to other effectors 20,21 , but their identities are unknown. Chemotaxis may also explain how parasites in the mammalian host disperse from the bloodstream into other tissues [42][43][44] .…”
Section: Discussionmentioning
confidence: 99%
“…The molecular and gene expression studies on Pratylenchus coffeae have been conducted to specify the genes (related to cell wall degrading enzyme) regulated in the presence and absence of root exudates, and it was observed that their activity changed with respect to the host-specific root exudate components provided for the assay ( Bell et al, 2019 ). The protozoan parasite Trypanosoma brucei generally displays its movement away from the other inhabited microbial groups; however, DeMarco et al (2020) have recently observed their positive chemotactic effect toward the colonized area of Escherichia coli . It is due to the presence of attractant that is a soluble, diffusible signal dependent on actively growing E. coli .…”
Section: Belowground Microbial Occurrence and Interactionsmentioning
confidence: 99%
“…This supports at least two signaling events: one to control SoMo initiation and a second to enable avoidance behavior. In a recent advance, DeMarco and colleagues provided the first evidence of positive chemotaxis (DeMarco et al., 2020). Using SoMo assays with procyclic T. brucei , they identified a behavior termed “BacSoMo,” in which parasites dramatically alter their movement toward bacteria (DeMarco et al., 2020).…”
Section: Environmental Cues and Cell Motilitymentioning
confidence: 99%
“…In a recent advance, DeMarco and colleagues provided the first evidence of positive chemotaxis (DeMarco et al., 2020). Using SoMo assays with procyclic T. brucei , they identified a behavior termed “BacSoMo,” in which parasites dramatically alter their movement toward bacteria (DeMarco et al., 2020). This study showed that procyclic forms are attracted to a soluble factor derived from living E. coli that acts at a distance to alter parasite motility.…”
Section: Environmental Cues and Cell Motilitymentioning
confidence: 99%